A review on the applications of wavelet transform in hydrology time series analysis - Sang, Yan-Fang (Atmospheric research, 2013)
In this paper, the wavelet transform methods were briefly introduced, and present researches and applications of them in hydrology were summarized and reviewed from six aspects. They include the wavelet aided multi-temporal scale analysis of hydrologic time series, wavelet aided deterministic component identification in hydrologic time series, wavelet aided de-noising of hydrologic time series, wavelet aided complexity quantification of hydrologic time series, wavelet cross-correlation analysis of hydrologic time series, and wavelet aided hydrologic time series simulation and forecasting. Finally, several personal opinions on the possible future researches of wavelet transform and its applications in hydrology were given from three aspects: methodical researches, further applications and combination. ► Wavelet analysis (WA) is an effective method for hydrologic time series analysis. ► Methodical researches should be further conducted for improving the WA method. ► The WA method can be increasingly applied in hydrology in the future. ► Coupling WA and other methods can be an effective approach for hydrologic series analysis.